(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The preparation of future physical education teachers requires not only the acquisition of professional knowledge and practical skills but also the development of personal competencies that ensure effective pedagogical activity. Modern educational reforms and the competence-based approach in higher education emphasize the importance of forming integrated professional and personal competencies among future specialists. The purpose of this study is to analyze the factors influencing the development of professional and personal competencies of future physical education teachers in the system of pedagogical education. The research examines pedagogical, psychological, organizational, and socio-cultural factors that contribute to the formation of professional readiness among students of physical education faculties. Particular attention is given to the role of modern pedagogical technologies, independent learning activities, practical training, and the educational environment of higher education institutions. The study also considers the impact of motivation, reflective thinking, communication skills, and professional values on the development of future teachers. The findings indicate that the effective integration of theoretical knowledge with practical experience significantly enhances the professional competence of students. Moreover, the creation of an innovative educational environment, the use of interactive teaching methods, and the systematic organization of independent learning activities contribute to the formation of responsible, creative, and professionally oriented specialists. The results of the study demonstrate that a comprehensive pedagogical approach combining educational content, methodological support, and active student participation is essential for developing the professional and personal competencies of future physical education teachers.